1995
DOI: 10.1093/oxfordjournals.aje.a117478
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Transforming Growth Factor Alpha (TGFα) TaqI Polymorphismand Oral Clefts: Indication of Gene-Environment Interaction in a Population-based Sample of Infants with Birth Defects

Abstract: In this study of infants with isolated birth defects, 69 cleft palate only cases, 114 cleft lip with or without cleft palate cases, and 284 controls with noncleft birth defects (all born in Maryland between 1984 and 1992) were examined to test for associations among maternal exposures, genetic markers, and oral clefts. A significantly higher frequency of positive family history of birth defects among both groups of oral cleft cases compared with controls was seen in these data. While there was a modest increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 208 publications
(126 citation statements)
references
References 0 publications
2
116
0
8
Order By: Relevance
“…In addition, they reported a significantly increased risk of CP associated with the potential interaction between mothers who smoked during pregnancy and infants who carried the rarer C2 allele at the TGFA Taq1 site (odds ratio [OR]: 8.69; 95% confidence interval [CI]: 1.57-47.8). 23 Findings from this study were replicated in an investigation in California 24 but not in investigations in Iowa 25 or Denmark. 26 In these latter studies, however, a family history of clefting was found more frequently among case than among control children.…”
Section: Family History As An Established Risk Factormentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, they reported a significantly increased risk of CP associated with the potential interaction between mothers who smoked during pregnancy and infants who carried the rarer C2 allele at the TGFA Taq1 site (odds ratio [OR]: 8.69; 95% confidence interval [CI]: 1.57-47.8). 23 Findings from this study were replicated in an investigation in California 24 but not in investigations in Iowa 25 or Denmark. 26 In these latter studies, however, a family history of clefting was found more frequently among case than among control children.…”
Section: Family History As An Established Risk Factormentioning
confidence: 65%
“…Although a detailed review of these studies is beyond the scope of this discussion, use of selected examples highlights their commonalities. Hwang et al 23 examined the risk of clefting associated with a family history of birth defects, maternal smoking, and variants in the transforming growth factor ␣ gene (TGFA) among case and control children delivered in Maryland from 1984 through 1992. They found a significantly higher frequency of family history of birth defects among case children compared with control children.…”
Section: Family History As An Established Risk Factormentioning
confidence: 99%
“…TGFA is the most extensively studied gene for gene-environment interaction effects on oral clefts. Significant interaction between TGFA TaqI variant and maternal smoking was first reported by Hwang et al (1995) by analyzing data from a case-control study in Maryland, US. An increased risk for CPO (OR = 7.02, 95% CI: 1.78-27.6) was observed in smoking mothers with infants carrying the TGFA TaqI C2/C2 genotype.…”
Section: Developmental Genes For Oral Clefts Transforming Growth Factmentioning
confidence: 97%
“…The combination of smoking and the uncommon variant of the gene raises the odds ratio to a highly significant level (Hwang et al, 1995). Another example is the gene-environment interactions that mediate the effects of organophosphate pesticides (Costa et al, 2005).…”
Section: Intrinsic Factorsmentioning
confidence: 99%